Pelatihan Keterampilan Tata Boga sebagai Bekal Usaha Mandiri bagi Warga Binaan Lapas Kelas III Rangkasbitung - Erfiyansyah, Ima; Rizaldi, Ahmad; Fauzi, Ahmad (Al-DYAS, 2025)
Inmates in correctional institutions represent a segment of society requiring continuous development to prepare for post-sentence social reintegration. This study aims to examine the implementation and outcomes of self-employment skills training through culinary workshops, specifically targeting inmates at Lembaga Pemasyarakatan Kelas III Rangkasbitung. The method used is participatory with a descriptive approach. The study involved 20 inmate informants, comprising 4 women and 16 men. Data analysis techniques included data reduction, data presentation, and conclusion drawing. The training program focused on the preparation of kimbab as a form of practical entrepreneurship development. The results indicate that the training positively impacted the improvement of inmates’ skills, as evidenced by the quality of the kimbab products and participants’ enthusiastic responses. Beyond technical success, the training fostered increased self-confidence, motivation for independent living, and readiness among inmates to contribute productively to society after release. These findings reinforce the urgency of developing practical skill-based training programs in correctional facilities as a sustainable strategy for empowerment and social reintegration.